EFFECT OF TRAINING, PEDAGOGIC COMPETENCY AND SELF DETERMINATION OF ORGANIZATIONAL COMMITMENT IN TEACHER ADMINISTRATION PROFESSION OF VOCATIONAL HIGH SCHOOL BUSINESS MANAGEMENT - Amusiana Amusiana; Thamrin Abdullah; Makruf Akbar (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2017)
The goal of the organization is to improve teachers on Teachers Professional Commitment Vocational High School Business Management Group Special Province of Jakarta, which is already running. In practice, the commitment of Profession in Vocational High School Teacher Business Group Management Special Province of Jakarta influenced Training, Competency Pedagogic and Self Determination. Issues to be addressed in this study is the effect of training, Pedagogic Competence and Self Determination of the Commitment to Profession in Vocational High School Teacher Business Group Management Special Province of Jakarta. The methodology used is survey research that tries to create a picture of systematic, factual and accurate information on the facts and the properties on a specific object. The sample used 109 teachers. In conclusion, the effect of training, Pedagogic Competence and Self Determination strong, it will create a Commitment to Profession in Vocational High School Teacher Business Group Management Special Province of Jakarta good. While the implications of their training, Pedagogic Competence and Self Determination is good, then it will create a Commitment to organization in Vocational High School Teacher Business Group Management Special Province of Jakarta reliable. Recommendations need to increase training, Pedagogic Competence and Self Determination that commitment Teachers organization in Vocational High School Business Management Group Special Province of Jakarta will be Optimized. Keywords :Training, Pedagogic Competency and Self Determination Of Organizational Commitment In Teacher Administration Profession.